1996
DOI: 10.1128/iai.64.1.298-304.1996
|View full text |Cite
|
Sign up to set email alerts
|

T-cell responses to outer membrane proteins of Neisseria meningitidis: comparative study of the Opa, Opc, and PorA proteins

Abstract: Former studies have shown that the class 5 outer membrane proteins (Opa and Opc proteins) of Neisseria meningitidis are at least as immunogenic as meningococcal porin proteins. High antibody titers to class 5 proteins have been observed in sera obtained during convalescence after meningococcal infection. A strong increase in anti-class 5 antibodies has also been observed in vaccinees who received a meningococcal outer membrane vesicle preparation. The enhanced B-cell response to class 5 proteins may be due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 33 publications
1
22
1
Order By: Relevance
“…Opa proteins (26^30 kDa) are immunogenic but highly variable [24]. Our results show that Opa proteins are present in ¢ve of six N. meningitidis strains tested, but their expression di¡ers between strains (two or three Opa proteins are expressed depending on strain).…”
Section: Discussionmentioning
confidence: 76%
“…Opa proteins (26^30 kDa) are immunogenic but highly variable [24]. Our results show that Opa proteins are present in ¢ve of six N. meningitidis strains tested, but their expression di¡ers between strains (two or three Opa proteins are expressed depending on strain).…”
Section: Discussionmentioning
confidence: 76%
“…Of the 40 18-mer peptides overlapping by 12 amino acids tested as T-cell helper epitopes by Wiertz et al (1996), those which most uniformly stimulated human Tcell proliferation were located in predicted transmembrane strands 1, 3, 4, 6 and 7 (peptides 2, 9, 16, 23 and 26)…”
Section: Resultsmentioning
confidence: 99%
“…The identification of five permissive sites which do not prevent folding and which are exposed on the cell surface raises the possibility of using the Opc protein in vaccine development as a carrier protein for epitopes from foreign antigens. The Opc protein is known to be highly immunogenic in humans (de Cossio et al, 1992;Rosenqvist et al, 1993) and contains several strong T-cell epitopes in transmembrane strands which stimulate proliferation of human T cells (Wiertz et al, 1996), unlike many other OMPs for which immunogenicity has only been tested in animal models. Experiments would be needed to determine which of the permissive sites would be most efficient at presenting foreign epitopes to the immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 17-kDa lipoprotein derived from the membrane of Francisella tularensis was reported to activate T cells which could produce IL-2 and interferon (IFN)-y (16). Recently, Wiertz et al (18) reported that human T cells responded to the outer-membrane proteins of Neisseria meningitidis. These findings indicate that the cellular immune response to bacterial membrane proteins may play a role in protection against infection.…”
Section: Introductionmentioning
confidence: 99%